1999
DOI: 10.1002/(sici)1097-0185(19990201)254:2<298::aid-ar16>3.3.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical study of Magellanic penguin (Spheniscus magellanicus) minor salivary glands during postnatal growth

Abstract: The histological and histochemical features of the minor salivary glands during postnatal development have been generally associated with the type of food ingested. However, recent studies support the fact that these salivary glands develop independently of the diet; in fact, minor salivary glands have similar morphological and histochemical characteristics in adult individuals of species with different diet regimens. Thus, the aim of this study was to characterize the developmental morphology of the penguin m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Although the most common type of gland found in all domestic and wild bird species is the tubular type, researchers have also identified simple branched tubulo‐alveolar, alveolar and complex alveolar glandular structures in birds (Samar et al . ; Crole and Soley ). It has been reported that, in the emu and ostrich, the palate has two regions, one glandular and the other aglandular, which are located rostrally and caudally to the choanal cleft.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Although the most common type of gland found in all domestic and wild bird species is the tubular type, researchers have also identified simple branched tubulo‐alveolar, alveolar and complex alveolar glandular structures in birds (Samar et al . ; Crole and Soley ). It has been reported that, in the emu and ostrich, the palate has two regions, one glandular and the other aglandular, which are located rostrally and caudally to the choanal cleft.…”
Section: Discussionmentioning
confidence: 96%
“…Only a limited number of studies are available on the anatomical and histological structure of the avian palate (Samar et al . , , ; Tivane ; Igwebuike and Eze ; Crole and Soley ; Erdogan and Alan ). It has been reported that in the ostrich, the anterior two‐thirds of the hard palate is divided by a median longitudinal mucosal fold into two regions, which lack papillae, whilst the caudal portion and the periphery of the choanal cleft contain small and fine papillae (Tadjalli et al .…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations